1985
DOI: 10.1080/14640748508401172
|View full text |Cite
|
Sign up to set email alerts
|

Matching and Oddity Learning in the Pigeon: Transfer Effects and the Absence of Relational Learning

Abstract: Three experiments examined the extent to which pigeons trained on a matching or oddity discrimination with one pair of colours showed transfer when tested on a new matching or oddity discrimination with a new pair of colours. Experiment 1 examined the effects of key spacing and a delay procedure and replicated previous reports that in the transfer stage subjects given the same kind of problem (Non-shift condition) in general learn more rapidly than those given the opposite problem (Shift condition). However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
35
3

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 18 publications
9
35
3
Order By: Relevance
“…The present experiment replicated the effect of overtraining on shift learning in matching-(or nonmatching-) to-sample discriminations observed in Nakagawa (2001 c) That is, the symmetry of transfer effect was obtained in the present experiment. This finding was in line with the expectation according to the findings of Nakagawa (2001 c), whereas it did not agree with the findings of Nakagawa (1992aNakagawa ( , 1993a using rats, nor the findings of Wilson et al (1985) using pigeons, nor the findings of Hogan (1974, 1975) using pigeons. This discrepancy in transfer effect among these experiments might be caused by an additional preshift training (i.e.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The present experiment replicated the effect of overtraining on shift learning in matching-(or nonmatching-) to-sample discriminations observed in Nakagawa (2001 c) That is, the symmetry of transfer effect was obtained in the present experiment. This finding was in line with the expectation according to the findings of Nakagawa (2001 c), whereas it did not agree with the findings of Nakagawa (1992aNakagawa ( , 1993a using rats, nor the findings of Wilson et al (1985) using pigeons, nor the findings of Hogan (1974, 1975) using pigeons. This discrepancy in transfer effect among these experiments might be caused by an additional preshift training (i.e.…”
Section: Discussionsupporting
confidence: 77%
“…The results had suggested that the rate of shift learning between shifted animals and nonshifted ones depended on whether they were tested with matching-to-sample or nonmatching-to-sample discriminations. That is, Wilson et al (1985) found the asymmetry of transfer effect in pigeons. They had claimed that the cause of this transfer effect seemed likely to be related to inherent bias toward the odd stimulus that occurred in both Phase 1 training and Phase 2 shift.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Following the demonstration that the shifted-nonshifted effect resulted from the OPE, Wilson et al (1985a) concluded, "When pigeons are transferred to novel stimuli, they characteristically revert to their oddity preference, and so it seems that even birds that have previously learned to ignore their preference may revert to it with novel stimuli" (p. 308). This statement implies that any novel-stimulus transfer may be due to an inadvertent OPE rather than a so-called higher order or relational comparison between the sample stimulus and the correct comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Wilson, Mackintosh, & Boakes (1985) reported that pigeons could learn stimulus-specific conditional discrimination but not abstract same/different rules in a matching-to-sample task. had similar results for a same/different discrimination task of two stimuli, when a small number of training stimuli were used, but pigeons possibly applied abstract same/different rules for novel stimuli when trained with large stimuli sets.…”
Section: Discussionmentioning
confidence: 99%